Wideoideologia i Youtubizacja jako narzędzia politycznego public relations (Politeja, 2013)
Video‑ideology and Youtubization as a Political Tool of Public RelationsQuantifier of our century is the media that define the present century as a time of media democracy, or, more narrowly, of e‑democracy. Politicians around the world submitting their political campaigns, interviews, speeches to the plans of media. They need media to communicate with the citizens of their countries, with voters, with national and international institutions. Models of communication created this way, according to the theory of public relations, can have the character of propaganda, marketing or of a dialog. The phenomenon of video‑ideology and the resulting political youtubization analyzed by the Author fits in all these three models. The paper identifies three channels of PR communication of the world of politics to the world of audience/electorate. The first two channels are top‑down schemes, created by the political power base, applied to influence and shape political attitudes of citizens. The third channel is bottom‑up formed grassroots citizens’ attitude, which is a meaningful response of the electorate to the political action.